PENGARUH PERSEPSI PETANI TERHADAP PEMANFAATAN ALSINTAN TRAKTOR TANGAN RODA DUA BERBASIS UPJA DI DESA PANGGUNGHARJO KECAMATAN SEWON KABUPATEN BANTUL DAERAH ISTEMEWA YOGYAKARTA - Nasoi, Arif (Jurnal Ilmu-Ilmu Pertanian, 2019)
This study aims to determine the perception of farmers about the Business Services of Tools and agricultural Machinery (UPJA) and agricultural machinery hand tractors two wheel as well as the influence of the perception of farmers towards utilization of agricultural machinery tractor the two wheel hand based UPJA which was held February 18 June 31, 2019 in Panggungharjo Village, Sub District of Sewon. Method data collection using questionnaire and analysis of documents. Sampling method used slovin with an error rate 15%. Data was analysed using simple linear regression. The results of the study shows the perception of farmers about agricultural machinery and UPJA in the category appropriate to the achievement value of 79.5%, based on the indicator of the attitudes and expectations derived category of right with the achievement of the value of each 79,8% and 82,7%, interest in the category is very appropriate with the achievement values of 87.5% and a motive in the category quite right with the achievement score of 68%. The results of the simple linear regression analysis showed a significant influence of the perception of farmers towards utilization of agricultural machinery tractor the two wheels hand based UPJA.